Postoperative PET/CT and target delineation before adjuvant radiotherapy in patients with oral cavity squamous cell carcinoma. (3rd September 2015) - Dutta, Pinaki R.; Riaz, Nadeem; McBride, Sean; Morris, Luc G.; Patel, Snehal; Ganly, Ian; Wong, Richard J.; Palmer, Frank; Schöder, Heiko; Lee, Nancy
Abstract: Background: The purpose of this study was for us to present our evaluation of the effectiveness of positron emission tomography (PET)/CT imaging in postoperative patients with oral cavity squamous cell carcinoma (SCC) before initiating adjuvant radiation therapy. Methods: Treatment planning PET/CT scans were obtained in 44 patients with oral cavity SCC receiving adjuvant radiation. We identified target areas harboring macroscopic disease requiring higher radiation doses or additional surgery. Results: Fourteen PET/CT scans were abnormal. Thirteen patients underwent surgery and/or biopsy, increased radiation dose, and/or addition of chemotherapy. Eleven patients received higher radiation doses. Patients undergoing imaging >8 weeks were more likely to have abnormal results ( p = .01). One‐year distant metastases‐free survival was significantly worse in patients with positive PET/CT scans (61.5% vs 92.7%; p = .01). The estimated positive predictive value (PPV) was 38% for postoperative PET/CT scanning. Conclusion: We demonstrated that 32% of patients have abnormal PET/CT scans resulting in management changes. Patients may benefit from postoperative PET/CT imaging to optimize adjuvant radiation treatment planning. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1285–E1293, 2016